Application of Carbon Nanodots from Cocoa Husk Waste to Improve the Mechanical Properties of Cellulose-Carrageenan-Based Biodegradable Films - Fitri Nuraini Fadila; Esa Ghanim Fadhallah; Ahmad Sapta Zuidar; Teguh Setiawan; Gustaf Triyoga; Jihan Allya Syahar; Hersan Pratama Ashari; Precillia Regitha; Fathan Khanifadin; Wulan Nur Aisyah; Dea Meranda; Zaskia Rahma Andini (Biology, Medicine, & Natural Product Chemistry, 2025)
Biodegradable films made from natural materials such as cellulose and carrageenan are easily degradable but exhibit poor mechanical properties. Incorporating carbon nanodots (CDs) from cocoa husk waste has the potential to improve their mechanical properties. This study aimed to characterize CDs synthesized from cocoa husk waste and evaluate their mechanical properties of cellulose-carrageenan-based biodegradable films. The research stages include the isolation of cocoa husk cellulose, CDs synthesis, CDs characterization, biodegradable film preparation, and characterization of the mechanical properties of biodegradable films. The experimental design used was a Completely Randomized Design (CRD) with the treatment factor of CDs addition at six levels (0%, 1%, 3%, 5%, 7%, 9%) with three replicates. The results showed that the average size of cocoa husk CDs was 997 nm, and the absorbance peak was detected at 298 nm, validating that the CDs had been successfully synthesized with blue light emission. Incorporating CDs significantly affected the mechanical properties of the biodegradable film. Biodegradable cellulose-carrageenan-based films with the addition of CDs from cocoa husks had a thickness of 0.35–0.64 mm, tensile strength of 2.94–4.20 MPa, elongation of 36.51–63.28%, and elasticity of 6.00–9.45 MPa. The tensile strength and elongation values meet the JIS Z 1707 standard. Higher concentrations of CDs significantly improved tensile strength and elasticity, while reducing the thickness and elongation.